Edukasi Lima Tahapan Emosi Diri dengan Self Management pada Siswa Remaja SMP di Denpasar - Niluh Nyoman Tantri Swastikaningtyas; Ni Putu Dita Wulandari (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The five-stage emotional model—awareness, understanding, expression, regulation, and reflection—integrates both cognitive and social aspects of emotional regulation. Adolescents need support in recognizing their emotions (awareness) and understanding their causes before moving on to healthy expression and regulation strategies. These stages do not always occur in a linear order; individuals may experience them differently or simultaneously. Issues such as social inequality, low self-esteem, insecurity, and bullying often lead to emotional instability, which contributes to the growing number of suicide cases among adolescents. A proposed solution is to incorporate character education into adolescent learning—not only to support mental well-being during this critical developmental phase, but also to help students understand emotional stages and learn techniques for emotional control as a foundation for psychological resilience. Therefore, the goal of this community service program is to educate adolescents on the importance of recognizing the five stages of emotion and preventing internal and social conflicts. The ultimate aim is to help youth respond to emotions with greater self-management and self-evaluation skills.